Pengaruh Bubuk Talk dan Limbah Karbit Sebagai Substitusi Filler pada Campuran AC-WC - Biyanti, Alifia Cikha; Rezkiyanni, Annisa; Indrayani; Kosim (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2025)
Asphalt Concrete - Wearing Course (AC-WC) is one of the surface layers in the construction of highway flexible pavement. The composition consists of: asphalt, split stone, sand and stone ash. Asphalt serves as a filler of empty space between coarse, fine, and folder aggregates. The purpose of this study was to determine the Optimum of Asphalt Content (KAO) value used as a filler, Stability, Flow, VIM, VMA, VFA, and MQ in AC-WC asphalt mixtures using cement, talc powder and carbide waste as fillers. The uniqueness of the research on talc powder and carbide waste on AC-WC asphalt mixtures is to reduce and utilize carbide waste that is no longer used and utilize talc powder as an additional filler binder or material. Marshall testing using 6% Optimum of Asphalt Content (KAO) with variations of cement, talc powder and carbide waste of 0% Cement; 100% BTLK, 25% Cement; 75% BTLK, 50% Cement: 50% BTLK, 75% Cement; 25% BTLK, and 100% Cement; 0% BTLK. From the results of this test, it was found that a mixture of cement, talc powder and carbide waste in the ratio of 75%; 25% will improve stability, flow, VFA and MQ.